The Crocodile, Ruler of the River - Tracqui, ValGerie; BIOS Agency (Watertown, MA : Charlesbridge, 2000)
Describes the physical characteristics, behavior, and habitat of crocodiles, as well as efforts to protect these creatures.
Includes bibliographical references (p. [28]).
Keywords: Crocodiles -- Juvenile literature; Crocodiles